Health and economic burden of rabies in northwest Ethiopia - Azalu, W.W.; Jemberu, Wudu T.; Taye, B.W.; Abebe, W.M.; Mekonnen, S.A. (Springer, 2025)
Background: Rabies remains a significant threat to both public health and economic stability across many developing countries. The challenge of effectively managing and preventing rabies is compounded by insufficient quantitative data regarding its financial and health consequences. Despite Ethiopia being one of the most-affected countries in the world, data on the public health and economic burden of rabies are limited.